Enhanced Ethanol Gas Sensor Performance through Adsorption Energy Analysis of Gd-Doped LaFeO3 with rGO Coating: A Density Functional Theory Study - Ibrohim, Maulana; Setiawan, Andhy; Waslaluddin, Waslaluddin; Mauludin, Taufik Syah; Suhendi, Endi; Aminudin, Ahmad (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
LaFeO3 (LFO) is commonly used as a material for gas sensor applications. However, the LFO material in ethanol gas sensor applications can still improve sensitivity and selectivity parameters. Gadolinium (Gd) doping is widely used in gas sensor applications to increase the sensitivity of gas sensors. In addition, reduced graphene oxide (rGO) materials are commonly used in gas sensor applications to increase gas sensors' selectivity, sensitivity, and working temperature. This study analyzed the effect of Gd doping (LGFO) and the addition of an rGO single layer on LFO material (LGFO@rGO) on sensitivity and selectivity based on the adsorption energy of the system with ethanol gas molecules. Density Functional Theory studies were conducted to yield insight into the LGFO or LGFO@rGO – ethanol gas interactions and the sensitivity and selectivity improvement by changing adsorption energy. Based on the analysis, the presence of Gd doping and single-layer rGO could increase the adsorption energy. The addition of the rGO layer showed an escalation of the adsorption energy of about 9.45%, 2.49 eV in the LGFO to -2.75 eV LGFO@rGO. This improved adsorption capacity translates to a higher sensitivity for detecting lower concentrations of ethanol gas. This result shows the potential of LGFO and LGFO@rGO as ethanol gas sensor materials.